2022
DOI: 10.3389/fneur.2022.1019036
|View full text |Cite
|
Sign up to set email alerts
|

High-risk features of basilar artery atherosclerotic plaque

Abstract: IntroductionHigh-resolution magnetic resonance imaging (HR-MRI) is used to characterize atherosclerotic plaque. The present study aimed to determine the high-risk features of the basilar artery (BA) atherosclerotic plaque.MethodsPatients with advanced BA stenosis were screened. The features including the ruptured fibrous cap (RFC), lipid core, intraplaque hemorrhage (IPH), plaque enhancement, and calcification were assessed by using high-resolution MRI. The relationship between the features and acute infarctio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…HRMRI can provide insight into the underlying vascular biological differences between symptomatic and asymptomatic MCA stenoses, which can help stratify stroke risk and modify treatment strategies. For the posterior circulation, rupture FC and IPH of basilar artery plaques are independent risk factors for acute infarction [ 52 ]. One study [ 22 ] found that some patients with posterior circulation infarction had vertebrobasilar artery atherosclerosis on HRMRI, but digital subtraction angiography (DSA) was normal, suggesting that infarction may be due to penetrating artery disease secondary to vertebrobasilar artery atherosclerosis.…”
Section: Hrmri Of Intracranial Atherosclerotic Diseasementioning
confidence: 99%
“…HRMRI can provide insight into the underlying vascular biological differences between symptomatic and asymptomatic MCA stenoses, which can help stratify stroke risk and modify treatment strategies. For the posterior circulation, rupture FC and IPH of basilar artery plaques are independent risk factors for acute infarction [ 52 ]. One study [ 22 ] found that some patients with posterior circulation infarction had vertebrobasilar artery atherosclerosis on HRMRI, but digital subtraction angiography (DSA) was normal, suggesting that infarction may be due to penetrating artery disease secondary to vertebrobasilar artery atherosclerosis.…”
Section: Hrmri Of Intracranial Atherosclerotic Diseasementioning
confidence: 99%
“…In contrast, HR-MRI demonstrates the capacity to visualize the fibrous cap effectively. Instances of fibrous cap rupture are identifiable by the presence of partially obscured and irregular surfaces within T 1 -weighted or T 2 -weighted images (157).…”
Section: Morphological Parametersmentioning
confidence: 99%